Debriefing Program of Digital Literacy-oriented Teaching Material Development for Prospective Physics Teacher Students in the MBKM-Teaching Assistant Program - Rahmawati, Rahmawati; Syamsuddin, Agustan; Nurlina, Nurlina (KnE Social Sciences, 2024)
This study aims to develop a debriefing program for prospective physics teacher students in order to develop digital literacy-oriented learning tools through the independent learning campus program - teaching assistance program (MBKM - Teaching Assistance Program). One of the converted courses in the teaching assistant program is the development of learning tools. The debriefing model given to students is in the form of project-based debriefing. The Reeves design-based research (DBR) model was used as the research design, and the data were processed descriptively. A field needs analysis was conducted on students who had taught in schools through the analysis of learning aids and questionnaires. The participants in this study were 18 students who are prospective physics teachers and also members of the Teaching Assistance Program. The research stages are needs analysis, curriculum analysis, lesson plan design for material analysis, and learning assessment. All forms of projectbased assignments were directed at the development of digital literacy-oriented teaching materials. The results of the research were in the form of stages of debriefing, debriefing materials, and procedures for application debriefing programs. In addition, the results of the limited trial showed that students tend to have digital literacy skills in the medium category. They are already proficient with several applications in designing interesting and correct teaching materials. Keywords: digital literacy, prospective physics teacher, MBKM-teaching